Does Fetal Malnutrition Affect Ghrelin, Leptin, Adiponectin and Insulin Levels in the Cord Blood of Newborns? - Sema Tanrıverdi; Betül Ersoy; Fatma Taneli; Esra Özer (Galenos Yayinevi, 2022)
Aim:Fetal malnutrition is a condition characterized clinically by the inability of subcutaneous adipose tissue and muscle mass to reach the normal amount or by significant intrauterine loss. The major hormones regulating fetal growth, fetal energy metabolism and adipogenesis are insulin, leptin, ghrelin and adiponectin. Cholesterol and triglycerides are very important in fetal growth in the last period of pregnancy. In this study, it was aimed to compare the glucose, insulin, leptin, ghrelin, adiponectin, cholesterol and triglyceride levels in the cord blood of newborn babies with and without fetal malnutrition.Materials and Methods:Term babies born in our hospital were included in this study. Babies with a Clinical Assessment of Nutritional Status of 24 or below were considered as cases with fetal malnutrition, and those over 24 were considered as cases without fetal malnutrition. Glucose, insulin, leptin, ghrelin, adiponectin, total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, very-low-density lipoprotein cholesterol and triglyceride levels were studied from blood samples taken from the umbilical cord after delivery.Results:A total of 80 term newborn babies (40 babies with fetal malnutrition and 40 babies without fetal malnutrition) were included in this study. Birth weight, glucose and insulin values were found to be significantly lower in the group with fetal malnutrition (p<0.001; p<0.001; p=0.047, respectively), and adiponectin levels were found to be significantly higher (p<0.001).Conclusion:In our study, adiponectin levels in cord blood were found to be high in infants with fetal malnutrition. Considering the antiinflammatory role of adiponectin, high adiponectin levels in infants with fetal malnutrition may directly or indirectly reflect a protective mechanism.